Adoption and Impact of Digital Learning: Insights from Educational Research - J. S., Gopika; R.V, Rekha (Indian Journal of Educational Technology, 2025)
This comprehensive study explores the field of digital learning, following its development from Jay Cross’s ground breaking theories in 1999 to its current use and effects on educators and students. The study looks at the fundamentals of digital learning, adoption rates, and the attitudes and opinions of educators and students. It examines the various elements that affect the effective integration of digital learning, including the acceptance of new technologies, instructional approaches, and socioeconomic differences. In addition, it evaluates how the COVID 19 pandemic affected digital learning, explaining the difficulties and possibilities it brought to the field of education. The study emphasises the significance of digital infrastructure, teacher training, and curricular integration in improving digital learning experiences. It emphasises the need to address hurdles, including uneven access to technology, teacher preparedness, and socioeconomic inequality, in order to promote a more inclusive digital learning environment. The paper also makes recommendations for ways to enhance digital learning for teachers and students, focusing on interactive platforms, thorough evaluation techniques, and ongoing improvement goals. Additionally, the study points out important directions for further investigation, such as the ways in which digital learning might advance inclusion and equality, how well it works for kids with special needs, and how it affects students’ social-emotional learning outcomes. The collective outcome of this study endeavours to direct decision-makers, instructors, and interested parties towards improving digital learning methodologies, guaranteeing their effectiveness, inclusiveness, and involvement in the educational environment.